Modern database management / Jeffrey A. Hoffer, Mary B. Prescott, Fred R. McFadden - Hoffer, Jeffrey A.; McFadden, Fred R. 1933-; Prescott, Mary B. (Pearson Education Limited, 2011)
Focusing on what leading database practitioners say are the most important aspects to database development, Modern Database Management presents sound pedagogy and includes topics that are critical for the practical success of database professionals. This text also continues to guide students into the future by presenting research that could reveal the "next big thing" in database management.